A Study of the Role of Behavioural Finance in Investment Decision Process of Individual Investors with Reference to Behavioural Finance Theories’ Effect on Investors (International Journal of Innovative Research in Engineering & Management, 2022)
Investment decisions are always crucial.  Lots of financial gains anticipations are included in  investment decisions. Investors make different calculation  before investing. Yet, the investment decisions are not  always based up on financial calculation only. Investors  become influenced by other concerns like imitation of peer  group, advise of elders etc. Studying such influencing factors  is subject matter of behavioural finance. In the present study  the researchers have focused upon the behavioural finance  theories as a determinant of the investment decisions.  Researchers have used different behavioural finance theories  to establish constructs. A questionnaire has been developed  to test the different aspects of investment decisions. The  reliability analysis (Cronbach's Alpha 0.751) of the  questionnaire has been conducted. Further the questionnaire  extracted 10 variables. These have been named as Individual  Investors’ Investment Decisions, Risk Consideration, Value  consideration, Fear of Missing Opportunity, Regret  Aversion, Psychological Influence, Cognitive Dissonance,  Emotion of Investor, Over Reactive Instinct, Under Reactive  Instinct. These variables have been tested for corelation and  further multiple corelation coefficient. R value 0.786  suggested the established variable has significant impact on  each other.
Keywords: Behavioural finance; Investment decisions; Prospect theory; Heuristic Theory; Over and under theory; Regret theory